2009
DOI: 10.1007/s10658-009-9524-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent, symptomless, systemic, and seed-borne infection of lettuce by Botrytis cinerea

Abstract: Experiments are presented which show that Botrytis cinerea, the cause of grey mould disease, is often present in symptomless lettuce plants as a systemic, endophytic, infection which may arise from seed. The fungus was isolated on selective media from surface-sterilised sections of roots, stem pieces and leaf discs from symptomless plants grown in a conventional glasshouse and in a spore-free air-flow provided by an isolation propagator. The presence of B. cinerea was confirmed by immuno-labelling the tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 29 publications
(41 reference statements)
2
73
0
5
Order By: Relevance
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, ; Sowley et al ., ; Grant‐Downton et al ., ; Shaw et al ., ). Shaw et al .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, several Botrytis species were shown to exhibit endophytic stages in their lifecycles in a range of flowering plants (Barnes & Shaw, ; Sowley et al ., ; Grant‐Downton et al ., ; Shaw et al ., ). Shaw et al .…”
Section: Discussionmentioning
confidence: 98%
“…This is all consistent with endophytic growth for extended periods (Barnes and Shaw, ). A similar pattern was found for cyclamen (in which isolates could be recovered from the interior of the corm), and then for lettuce; in each case, there was evidence that infected seeds could give rise to systemically infected plants (Sowley et al ., ).…”
Section: ‘Let's Play Hide and Seek’mentioning
confidence: 97%
“…In lettuce, seed‐borne infection moved first to roots, and then stems; the lowest frequency of isolation was from leaves. Botrytis ‐specific monoclonal antibody labelling of whole mounts of lettuce root, stem and leaf sections detected internal hyphal spread within roots and above‐ground parts (Sowley et al ., ). These and other data suggest the following life cycle: young seedlings or seeds are infected by spores; the resulting mycelium grows actively for weeks or months in an association which is at least partly inside the host; when the host flowers, the lifestyle changes to an aggressive attack (Barnes and Shaw, ); abundant spores are produced which infect seed heads and/or seedling plants, and the cycle is repeated.…”
Section: ‘Let's Play Hide and Seek’mentioning
confidence: 97%
See 1 more Smart Citation
“…In general, B. cinerea is considered to be a necrotroph, which draws nourishment from dead host tissue and produces initially local (‘primary’) necrotic lesions, which subsequently expand to actively cause plant tissue decomposition (Horst, ; Jarvis, ; Coertze & Holz, ; Elad et al ., ). In contrast, recent studies have revealed that B. cinerea can also cause symptomless systemic infection in several host plants including Primula spp., lettuce ( Lactuca sativa ), Arabidopsis thaliana and Taraxacum vulgare (Barnes & Shaw, ; Rajaguru & Shaw, ; Sowley et al ., ; Shaw et al ., ). In this type of infection the fungus grows along with the plant and enters newly expanding organs, without producing symptoms, until the plant becomes physiologically susceptible, typically at flowering.…”
Section: Introductionmentioning
confidence: 98%